Breast cancer associated with intraductal papilloma - Yu. I. Gaman; V. I. Apanasevich; A. V. Laguryova; O. M. Zagrutdinova; N. G. Plekhova; O. A. Argishev; V. I. Nevozhay; Е. P. Kostiv (Опухоли женской репродуктивной системы)
Background. Intraductal papilloma (IDP) is not usually considered as an obligate precancerous lesion since the cases of its progression into cancer are exceedingly rare.Aim. To analyze the impact of IDP on the risk of breast cancer in the future.Materials and methods. This retrospective study included patients aged 22–82 years operated on for IDP (n = 304) and other benign breast tumors (n = 304) between 2014 and 2022. We checked these patients in the cancer registry of Primorsky Regional Oncology Dispensary to find out whether any of them developed any type of cancer, including breast cancer. Then we calculated the odds of developing breast cancer in both groups.Results and conclusion. We found that paients with a history of IDP are 2.4 times more likely to develop breast cancer. The incidence of other cancer types did not differ significantly between the two groups. Our findings are consistent with the results of similar foreign studies and might indicate that IDP and breast cancer share the same etiological factor. They can also highlight specific characteristics of asymptomatic IDP.